Disseminating and constructing academic knowledge in online scholarly journals: An analysis of virtual special issue introductions. (August 2018) - Mur-Dueñas, Pilar
Abstract: Digital media are promoting the appearance of new genres and practices which contribute to the construction and dissemination of academic knowledge in English, which is used as a vehicle for global communication. International online scholarly journals in some areas are collecting previously published articles in that same journal on a particular topic as a Virtual Special Issue (VSI), presented by an Introduction by its editors. It is the aim of this paper to explore this new academic digital genre by analysing the communicative purpose and the rhetorical macrostructure of a corpus of VSI Introductions in the field of Business Management and Marketing. Interpersonality features will be explored to unveil how they help VSI Introduction authors to portray themselves as knowledgeable members of the discipline to a potentially heterogeneous audience as well as to create a positive image of the journal, making it a prominent site of publication in the field. The digital medium allows journals in general and editors and authors of the published texts in particular to gain e-visibility allowing for the dissemination of academic knowledge in a global context through new academic genres.